Using the project management maturity model : strategic planning for project management - Kerzner, Harold (John Wiley & Sons, Inc., 2019)
The industry validated Project Management Maturity Model developed by Dr. Harold Kerzner--updated and expanded Using the Project Management Maturity Model offers assessment tools for organizations of all sizes to evaluate their progress in effectively integrating project management along the maturity curve. This Third Edition includes maturity metrics, examples of Project Management Maturity Model (PMMM) reports, a new chapter on the characteristics of effective PMMM, assessment questions that align with the PMBOK ® Guide--Sixth Edition, all-new illustrations that define advanced levels of maturity, assessment tools for organizations using traditional PM methods, and detailed guidance for organizations using Agile and Scrum. Using the Project Management Maturity Model: Strategic Planning for Project Management, Third Edition is broken down into three major parts. The first part discusses the principles of strategic planning and how it relates to project management, the definition of project management maturity, and the need for customization. The second part details the Project Management Maturity Model (PMMM), which provides organizations with general guidance on how to perform strategic planning for project management. The third part of the book looks at some relatively new concepts in project management such as how assessments can be made to measure the firm's growth using PM 2.0 and PM 3.0. Features customizable maturity model assessment tools for organizations of all sizes Includes assessment questions updated to line up with PMBOK® Guide--6th Edition Offers detailed guidance on applying the maturity model for Agile and Scrum Includes PowerPoint decks to aid in teaching the maturity model Using the Project Management Maturity Model: Strategic Planning for Project Management, Third Edition is an ideal book for senior level and middle level corporate managers, project and team managers, engineers, project team members, and business consultants. It also benefits both business and engineering students in courses on advanced project management.